Secondary School Dropout: Causes and Consequences - Peña Lovera, Kathia Jackeline (2025)
Secondary school dropout remains a major educational challenge, deeply affecting equity and socioeconomic development. This systematic review synthesized research from 2000 to 2025 to identify the main causes, consequences, and effective interventions. Using PRISMA guidelines and thorough database searches, 37 studies (32.5% inclusion rate) were included in the analysis. Results showed that socioeconomic factors (70% of studies), school-related issues like punitive practices, and family background are key causes. Consequences include social exclusion and reduced human capital. The most effective interventions combine economic support, school improvement, and school–family partnerships. The evidence confirms school dropout is multicausal and systemic, needing coordinated, context-sensitive policies.